Next Speakers Plan Their Turn Early and Speak after Turn-Final “Go-Signals” - Barthel, Mathias; Meyer, Antje S.; Levinson, Stephen C. (Frontiers in Psychology, 2017)
In conversation, turn-taking is usually ﬂuid, with next speakers taking their turn right after the end of the previous turn. One reason for this ﬂuency is early content planning of the next turn, if possible while the current turn is still coming in, as found by Barthel et al. (2016) using the list-completion paradigm. The present study makes use of the same paradigm, analyzing speech onset latencies and eye-movements of participants in a task-oriented dialogue with a confederate. Participants named objects visible on their computer screen in response to utterances that did or did not contain cues to the end of the incoming turn. Participants were found to start planning their response as early as possible, replicating the ﬁndings of Barthel et al. (2016), and to use turn-ﬁnal cues to turn-completion as ‘go-signals’ to initiate their response. The results are consistent with models of turn-taking that assume next speakers to start planning their response as soon as the incoming turn’s message can be understood and to monitor the incoming turn for cues to turn-completion so as to initiate their response when turn-transition becomes relevant.